Eksplorasi Faktor Sosial Budaya Terhadap Pengetahuan Masyarakat Tentang Suplemen dan Nutrisi Dalam Pencegahan Stunting di Desa Kesetnana - Azalya Sarifudin, Barbara; Nenogasu, Yeri Delsia; Tanggur, Fembrianus Sunario; Uli, Roy Pinta (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Stunting remains a complex chronic nutritional problem in Indonesia, particularly in rural areas where socio-cultural influences strongly affect dietary patterns and maternal-child health. This study aims to explore the socio-cultural factors that influence community knowledge and the utilization of supplements and nutrition in stunting prevention in Kesetnana Village, South Central Timor Regency, East Nusa Tenggara. A qualitative research design with a case study approach was used. The study population consisted of residents of Kesetnana Village, with 15 informants selected through purposive and snowball sampling, including pregnant women, breastfeeding mothers, Posyandu cadres, pharmacy personnel, health workers, community leaders, and traditional leaders.The main variables included knowledge about supplements and nutrition, socio-cultural factors, and the utilization of nutritional supplements. Data were collected through in-depth interviews, focus group discussions (FGD), participatory observation, and documentation, and analyzed using thematic analysis. The results showed that community knowledge about the function of supplements and nutrition was still limited; socio-cultural norms (such as food taboos and the role of traditional or family leaders) significantly influenced consumption behavior; and the use of supplements was not yet optimal. It is concluded that stunting prevention requires culturally sensitive education and the strengthening of pharmacists’ roles in collaboration with community leaders.